디자인 씽킹 기반 미용전공수업의 자기주도성, 학습만족, 학습성과에 관한 연구 - 김선형; Sun-hyoung Kim (한국미용학회지, 2024)
This study is an empirical analysis of how beauty major classes based on design thinking teaching methods affect self-direction ability, learning satisfaction, and learning outcomes. As a result of the study, self-direction, learning satisfaction, and learning performance improved compared to before the design thinking-based beauty major class, and learning attachment, self-confidence, openness, responsibility·autonomy for each sub-factor of self-direction showed a statistically significant positive (+) with learning satisfaction. It was found that there was a correlation, and learning attachment, self-confidence, openness, responsibility·autonomy for each sub-factor of self-direction were found to have a statistically significant positive (+) correlation with learning performance. Additionally, learning satisfaction was found to have a statistically significant positive (+) correlation with learning outcomes. As a result of conducting multiple regression analysis to verify the effect of self-direction on learning satisfaction and learning performance, learning attachment, responsibility·autonomy, and openness for each sub-factor of self-direction are important factors in learning satisfaction, and selfdirection is an important factor in learning performance. Openness and self-confidence were found to be important factors for each subfactor of initiative. As a result of conducting a simple regression analysis to verify the effect of learning satisfaction on learning performance, it was found that learning satisfaction is an important factor in learning performance. This study targeted 4th graders at a specific school, and a small number of people were selected as subjects, so it is difficult to generalize. Future research targeting a larger number of students and applying it to various classes will be needed.